Influence of tangible and intangible resources on office building performance in the Golden Triangle of Kuala Lumpur, Malaysia - Cheah, Jun Hwa (2016)
This study attempts to address problems faced by office building managers, that is the oversupply of office space in the Golden Triangle Kuala Lumpur (GTKL), which resulted in intense competition to sustain their building occupancy rate. Hence, this study addresses the issue by looking at how office building owners can enhance their office building performance (i.e., tenant satisfaction, tenant loyalty, willingness to pay and occupancy rate) by using tangible (i.e., office building offerings) and intangible resources (i.e., customer orientations and positioning strategies). By drawing on the Resource Based View Theory, this study proposes a conceptual framework that focuses on the relationship of i) responsiveness customer orientation (RCO) and proactive customer orientation (PCO) on tenant satisfaction, ii) mediating role of office building offerings on customer orientations (RCO & PCO) and tenant satisfaction, iii) moderating role of office building grading (i.e., Grade A vs Non-Grade A) on perceived benefits positioning strategies and willingness to pay, and lastly, iv) mediating role of tenant loyalty on the process performance (i.e., tenant satisfaction) and end-performance (i.e., willingness to pay and building occupancy rate). The questionnaire was distributed to tenants in 110 office buildings in the GTKL through multi-stage sampling technique (stratified sampling and judgemental sampling). A total of 380 tenants completed the questionnaire. In this study, the Variance Based-Structural Equation Modeling (VB-SEM) was used to analyse the data (Using SmartPLS 3.0). The outcome of this study suggested that two direct relationships (i.e., PCO on Tenant Satisfaction and Tenant Satisfaction on Willingness to Pay High Price) had positive associations in the study. Moreover, the findings revealed that office building offerings such as Building Features, Services and Management (BFSM) and location factors did mediate the relationship between customer orientations (RCO and PCO) and tenant satisfaction. In terms of office building grading (i.e., Grade A and Non-Grade A), this study found that grading did moderate the relationship between perceived-benefits positioning strategies (i.e., value for money, service, reliability and attractiveness) and willingness to pay. Drawing from the findings, it extends the RBV theory by defining resources basing on attention-based view theory, congruity theory, and social exchange theory. Practically, building managers are suggested to emphasize on PCO to seek future needs of tenants and incorporate these feedbacks into office building offering, which will then result in satisfaction. Furthermore, building managers of Grade A buildings are proposed to highlight perceived benefits like excellent services, reliability and attractiveness. In contrast, Non-Grade A buildings might want to focus on benefits like value for money.